Elaboration and characterisation of ZnO thin films - Benramache, S.; Benhaoua, B.; Khechai, N.; Chabane, F. (EDP Sciences, 2012)
Abstract – Highly transparent ZnO thin films have been prepared on microscope glass substrate using dip-coating technique. The films were obtained at a concentration of solgel solution is 0.5 M. The structural and optical properties of the ZnO thin films were studied as a function of the annealing temperature varying between 450 to 600 ◦C. From the XRD analysis, the whole obtained films have a hexagonal wurtzite structure with a strong (002) preferred c-axis orientation. The grain size increased with annealing temperature indicating an improvement in the crystallinity of the films. The average transmittance of all the films is about 70–80% as measured by UV-vis analyzer. The band gap increased with the increase of temperature from 3.25 to 3.42 eV. The decrease of the strain of ZnO films is probably due to an improvement of the crystallinity of the films. The best result is achieved at 600 ◦C.
Article
Keywords: ZnO; thin film; dip-coating; annealing temperature